Patient Empowerment by Increasing the Understanding of Medical Language for Lay Users - Topac, V.; Stoicu-Tivadar, V. (Methods of Information in Medicine, 2013)
Background: Patient empowerment is important in order to increase the quality of medical care and the life quality of the patients. An important obstacle for empowering patients is the language barrier the lay patient encounter when accessing medical information.Objectives: To design and develop a service that will help increase the understanding of medical language for lay persons.Methods: The service identifies and explains medical terminology from a given text by annotating the terms in the original text with the definition. It is based on an original terminology interpretation engine that uses a fuzzy matching dictionary. The service was implemented in two projects: a) into the server of a tele-care system (TELEASIS) with the purpose of adapting medical text assigned by medical personnel for the assisted patients. b) Into a dedicated web site that can adapt the medical language from raw text or from existing web pages.Result: The output of the service was evaluated by a group of persons, and the results indicate that such a system can increase the understanding of medical texts. Several design decisions were driven from the evaluation, and are being considered for future development. Other tests measuring accuracy and time performance for the fuzzy terminology recognition have been performed. Test results revealed good performance for accuracy and excellent results regarding time performance.Conclusion: The current version of the service increases the accessibility of medical language by explaining terminology with a good accuracy, while allowing the user to easily identify errors, in order to reduce the risk of incorrect terminology recognition.
Keywords: Terminology; language understanding; patient empowerment; NLP